Situation Report: Baltic Area, 4 March 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The 19th Estonian CP Congress / by Toomas Ilves Party Congress Focuses on Nationality Problems / by Toomas Ilves Another Alleged Recantation by Minister / by Toomas Ilves The 24th Latvian Communist Part Congress / by Dzintra Bungs "Openness" - But Not the Whole Truth / by Dzintra Bungs The 19th Lithuanian Communist Party Congress / by Saulius Girnius Priest Killed in Automobile "Accident" / by Saulius Girnius Five Lithuanians Tried for Printing Religious Materials / by Saulius Girnius Unfounded Criticism of Catholic Commitment to Temperance / by Saulius Girnius Debate on Private Plots / by Saulius Girnius